2009
DOI: 10.1200/jco.2008.17.8079
|View full text |Cite
|
Sign up to set email alerts
|

The Terrible Choice: Re-Evaluating Hospice Eligibility Criteria for Cancer

Abstract: Purpose To be eligible for the Medicare Hospice Benefit, cancer patients with a life expectancy of 6 months or less must give up curative treatment. Our goal was to determine whether willingness to make this choice identifies patients with greater need for hospice services. Patients and Methods Three hundred patients with cancer and 171 family members were recruited from six oncology practices. Respondents completed conjoint interviews in which their perceived need for five hospice services was calculated from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 31 publications
0
51
0
Order By: Relevance
“…A PPS of ≤60 is increasingly being used to assess eligibility for home care services based on the observation that this population requires more home support [1]. Assessing Physical distress subscore includes ESAS pain, fatigue, nausea, drowsiness, appetite, and shortness of breath items; psychological distress subscore includes anxiety and depression items a All p values are <0.001 eligibility for hospice or home care using performance status criteria may be more appropriate than using clinical assessment of prognosis, which is notoriously optimistic for both physicians and nurses [23,35], or willingness to give up curative treatment, which does not identify those with greater perceived need for services [8]. However, our study shows that physicians may rate patients as being healthier than nurses using the PPS scale, and this should be kept in mind when using the scale for this purpose.…”
Section: Discussionmentioning
confidence: 99%
“…A PPS of ≤60 is increasingly being used to assess eligibility for home care services based on the observation that this population requires more home support [1]. Assessing Physical distress subscore includes ESAS pain, fatigue, nausea, drowsiness, appetite, and shortness of breath items; psychological distress subscore includes anxiety and depression items a All p values are <0.001 eligibility for hospice or home care using performance status criteria may be more appropriate than using clinical assessment of prognosis, which is notoriously optimistic for both physicians and nurses [23,35], or willingness to give up curative treatment, which does not identify those with greater perceived need for services [8]. However, our study shows that physicians may rate patients as being healthier than nurses using the PPS scale, and this should be kept in mind when using the scale for this purpose.…”
Section: Discussionmentioning
confidence: 99%
“…31 In order to better identify patients who would benefit from hospice, modifications to the Medicare Hospice Benefit eligibility criteria have been proposed to include factors such as functional status, quality of life, and symptom burden. 32 Such an approach would address the many patients in this study whose health status and/or preferences indicated that they might benefit from hospice care but with whom their clinicians did not discuss hospice. The association between life expectancy and hospice discussion in this study suggests that clinicians would need clear guidelines about what should prompt a discussion about hospice care.…”
Section: Discussionmentioning
confidence: 99%
“…225 Prognostic estimates are notoriously optimistic, 226 which might delay the commencement of a palliative approach and increased support, particularly in countries such as the USA where hospice services are linked to a prognosis of less than 6 months. 227 Once PCPs are involved in palliative care, barriers at an organisational level might surface. Dutch PCPs reported that arrangement of home care services or procedures such as oxygen therapy, intravenous medications, or paracentesis is time-consuming and that extra care (eg, assistants to aid with care, such as nurses) is diffi cult to obtain.…”
Section: Barriers To Primary Palliative Carementioning
confidence: 99%